1.2: Invited Paper: Implementation of Full Panel IR‐Drop Simulation for AMOLED Display Using Current SPICE Toolkit. (28th November 2018) - Wang, Longyan; Jia, Xiyang; Zhao, Guohua; Fan, Longfei; Wu, Jianlong; Han, Zhenzhen; Hu, Siming; Ma, Zhanjie; Zhu, Hui; Zhu, Xiujian; Huang, Xiuqi
Abstract : The IR‐drop in the full AMOLED display panel caused by the pixel current is simulated within the mainstream SPICE toolkit to evaluate the display uniformity. Each electrical part of the display panel is simplified and equalized to allow the SPICE doing the very large scale calculation. The implementation of the full panel simulation and the results give better understanding of AMOLED panel design.